Sinkronisasi Peraturan Perundang-Undangan Tentang Kebijakan Bebas Visa Kunjungan - Erikson Sihotang (Universitas Mahendradatta, 2020)
In order to guarantee the benefits and protect various national interests as well as in the framework of upholding the state's sovereignty in the immigration sector, it is necessary to stipulate principles, supervision systems, service procedures for the entry and exit of people into and from the territory of Indonesia. The regulation on Visit Visa Free in Indonesian legislation is inconsistent with each other with the application of free visit visas on the basis of reciprocity and the principle of benefit. The Immigration Law stipulates that the granting of visa exemptions must pay attention to the principle of reciprocity and the principle of benefit, while the Presidential Regulation on Visit Visa Free stipulates that the purpose of granting visa exemptions for certain countries is in the framework of tourist visits. Thus, neither the reciprocity principle nor the benefit principle which is the basis for the consideration of granting visit visa exemptions has not been fulfilled in the policy of the Presidential Regulation on Visit Visa Free.